Step 1: Solve the second equation for y in terms of x
y = 3x - 4
Step 2: Substitute this expression for y into the first equation
-4x + 4(3x - 4) = -40
-4x + 12x - 16 = -40
8x - 16 = -40
8x = -24
x = -3
Step 3: Substitute x = -3 back into the second equation to find y
y = 3(-3) - 4
y = -9 - 4
y = -13
Therefore, the solution to the system of equations is (-3, -13).
Solve the system of equations by substitution.
−4x+4y=−40
y=3x−4
This question requires you to show your work.
Responses
(−3,−13)
open paren negative 3 comma negative 13 close paren - correct
(3, 7)
(3, 7)
- no response given
(6, 4)
(6, 4)
- no response given
(1,−1)
1 answer